2020
DOI: 10.1371/journal.pone.0240553
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine use in pediatric strabismus surgery: A systematic review and meta-analysis

Abstract: Background Common complications of pediatric strabismus surgery, including emergence agitation (EA), postoperative nausea and vomiting (PONV), and postoperative pain, may be prevented using dexmedetomidine, which is an anxiolytic and analgesic. This systematic review and meta-analysis assessed the effects of dexmedetomidine in patients who had undergone pediatric strabismus surgery. Method Five databases were searched for randomized controlled trials published from database inception to April 2020 that compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 41 publications
1
15
1
Order By: Relevance
“…Abbreviations: dexmed, dexmedetomidine administered intraoperatively; GI, gastrointestinal; MRI, magnetic resonance imaging; non-dexmed, no dexmedetomidine administered intraoperatively. There is growing evidence that dexmedetomidine is beneficial for reducing postoperative complications, including emergence agitation, 3,4,[14][15][16] pain, 16 opioid requirements, 2,5 and nausea. 16,17 These advantages continue to be demonstrated for common pediatric procedures, such as strabismus repair 17 and adenotonsillectomy, 14,15 and these recent reports have suggested that the reported benefits are realized without delaying recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abbreviations: dexmed, dexmedetomidine administered intraoperatively; GI, gastrointestinal; MRI, magnetic resonance imaging; non-dexmed, no dexmedetomidine administered intraoperatively. There is growing evidence that dexmedetomidine is beneficial for reducing postoperative complications, including emergence agitation, 3,4,[14][15][16] pain, 16 opioid requirements, 2,5 and nausea. 16,17 These advantages continue to be demonstrated for common pediatric procedures, such as strabismus repair 17 and adenotonsillectomy, 14,15 and these recent reports have suggested that the reported benefits are realized without delaying recovery.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that dexmedetomidine is beneficial for reducing postoperative complications, including emergence agitation, 3,4,[14][15][16] pain, 16 opioid requirements, 2,5 and nausea. 16,17 These advantages continue to be demonstrated for common pediatric procedures, such as strabismus repair 17 and adenotonsillectomy, 14,15 and these recent reports have suggested that the reported benefits are realized without delaying recovery. During the present study, dexmedetomidine was typically administered as a bolus dose at the start of the procedure, in the range 0.28 -0.51 µg/kg, but with higher doses in some cases, and the observed delay was relatively short: approximately an additional 5-7 minutes in the PACU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strabismus surgery is a typical pediatric procedure that involves general anesthesia. After strabismus surgery, many pediatric patients present with emergence delirium (ED), and the incidence rates are as high as 40-86% (1). ED can lead to various adverse effects, such as increasing risks of suture dehiscence or accidental removal of intravenous catheters, self-injury, prolonged postanesthesia care unit (PACU) length of stay, and even negative postoperative behavior (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, vitamin A palmitate (VAP) eye gel is applied for the treatment of dry eye in children after strabismus surgery, as surgery will cause adverse effects on the physiological structure of the ocular surface, and destroy the stability of the tear film, which will aggravate the postoperative discomfort because of the lack of tear lubrication (10). Compared with other dry eye drugs, such as sodium hyaluronate and Carbomer, VAP eye gel can not only play a role of replenishing water and lubricating the eyeball, but vitamin A supplementation can improve the dehydration symptoms of corneal and conjunctival epithelial cells, and promote the normal differentiation and proliferation of corneal epithelium and conjunctival epithelium (11).…”
Section: Introductionmentioning
confidence: 99%